Actinic Keratosis Pathogenesis Update and New Patents - Cantisani, Carmen; Paolino, Giovanni; Melis, Marcello; Faina, Valentina; Romaniello, Federico; Didona, Dario; Cardone, Michele; Calvieri, Stefano (Recent Patents on Inflammation & Allergy Drug Discovery, 2016)
Background: Actinic keratosis is a common premalignant skin lesion. Because of its increasing incidence, several efforts have been made to earlier detectection and to improve knowledge on photocarcinogenic pathways of keratinocytes. As a consequence, recently new discoveries have been done in this field. Objective: Starting from our previous review on actinic keratosis, we reviewed the literature focusing on pathogenesis and new patents in order to highlight the most recent progresses in diagnosis and therapeutic approach. Conclusion: Although several efforts have been done in the field of photodamaged skin, new upgrades in diagnosis and therapy are needed to detect superficial actinic keratosis earlier, to improve the disease free survival of patient and to better treat the field cancerization.
Keywords: inflammation